Stream vs block ciphers for scan encryption. (April 2019) - Valea, Emanuele; Da Silva, Mathieu; Flottes, Marie-Lise; Di Natale, Giorgio; Rouzeyre, Bruno
Abstract: Security in the Integrated Circuits (IC) domain is an important challenge, especially with regard to the side channel offered by test infrastructures. Test interfaces provide access to the internal states of the IC by means of the scan chains for testing and debugging purposes. In terms of security, however, scan chains are a potential source of leakage that can be exploited by attackers. A countermeasure against such attacks is to encrypt the data flowing through the scan chains. Two types of ciphers can be employed: stream ciphers or block ciphers. Both have pros and cons in terms of performance (footprint, impact on test activity) and security. In this paper, we present two solutions: one exploiting stream ciphers fulfilling security requirements, and another exploiting block ciphers. We draw a comparison between these two scan encryption countermeasures taking into account design cost functions and security properties.